2010
DOI: 10.1007/s10661-010-1415-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring seasonal bat activity on a coastal barrier island in Maryland, USA

Abstract: Research on effects of wind turbines on bats has increased dramatically in recent years because of significant numbers of bats killed by rotating wind turbine blades. Whereas most research has focused on the Midwest and inland portions of eastern North America, bat activity and migration on the Atlantic Coast has largely been unexamined. We used three long-term acoustic monitoring stations to determine seasonal bat activity patterns on the Assateague Island National Seashore, a barrier island off the coast of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Like other authors (e.g., JOHNSON et al 2011, VERBOOM & SPOELSTRA 1999), we did not detect a significant relationship between bat activity and humidity or wind speed. In the study area, the climate frequently varies more expressively in terms of temperature than in terms of humidity or wind speed (RAMBO 2000).…”
Section: Seasonal Variations In Bat Activity and Influence Of Climatisupporting
confidence: 77%
See 2 more Smart Citations
“…Like other authors (e.g., JOHNSON et al 2011, VERBOOM & SPOELSTRA 1999), we did not detect a significant relationship between bat activity and humidity or wind speed. In the study area, the climate frequently varies more expressively in terms of temperature than in terms of humidity or wind speed (RAMBO 2000).…”
Section: Seasonal Variations In Bat Activity and Influence Of Climatisupporting
confidence: 77%
“…Bats are highly active in forests and forest fragments in rural areas (ERICKSON & WEST 2003, LUMSDEN & BENNETT 2005, mainly in hedgerows and forest edges (RUSS et al 2003, PETTIT & WILKINS 2012, as well as around rivers, lakes, and lagoons (VAUGHAN et al 1997, BROOKS 2009). Furthermore, in temperate regions the activity levels of bats vary seasonally in response to fluctuations in climatic conditions and their own energy requirements throughout the year (CIECHANOWSKI et al 2010, JOHNSON et al 2011. Some studies highlighted the influence of abiotic factors on bat activity, such as temperature (HAYES 1997, RUSS et al 2003, wind speed (AVERY 1985, JOHNSON et al 2011, and relative humidity of the air (LACKI 1984, ADAM et al 1994.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cryan and Brown (2007) discovered longitudinal movement by hoary bats from inland summer ranges to coastal regions during autumn and winter and suggested that coastal regions with non-freezing temperatures may be important wintering areas for hoary bats. Off the coast of Maryland, Johnson et al (2011) recorded five species of bats, including eastern red bats, big brown bats (Eptesicus fuscus), hoary bats, tri-colored bats (Perimyotis subflavus), and silver-haired bats, on a barrier island and concluded these species used this island during migration, which could have implications for wind energy development near and offshore.…”
Section: Offshore Wind Facilitiesmentioning
confidence: 99%
“…Bats are present in the offshore environment in both Europe (Ahlen, Baagoe, and Bach 2009;Boshamer and Bekker 2008) and the USA (Cryan and Brown 2007;Johnson, Gates, and Zegre 2011;Grady and Olson 2006;Pelletier et al 2013;Hatch et al 2013), and have recently been detected at an OWED in the Netherlands (Poerink, Lagerveld, and Verdaat 2013). In the USA, the bats detected offshore have primarily been migratory tree bats (Cryan and Brown 2007;Grady and Olson 2006;Hatch et al 2013).…”
Section: Adverse Effects By Taxonomic Classmentioning
confidence: 99%